2020
DOI: 10.1159/000509644
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Abscess: An Unusual Presentation of COVID-19?

Abstract: Most patients with coronavirus disease 2019 (COVID-19) present with respiratory symptoms that range from mild symptoms to severe illness leading to mortality. Some might be asymptomatic and others may present with unusual presentations. A 55-year-old male with a past history of ischemic stroke, ischemic heart disease, and type 2 diabetes mellitus presented with right-sided weakness and a history of abdominal pain, diarrhea, and fever. He tested positive for COVID-19. Computed tomography (CT) abdomen showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…12 Al Ozaibi et.al 2020 in one of his research said that corona virus directly infect and damages the spleen leading to splenic abscess and also causes damage to other lymphoid tissues. 13 The cytokines are produced in response to infection by covid 19, there is excessive production of cytokines having antiviral action, the lymphocytes produces lymphokines. Jun-Ming Zhang, et.al 2007 in one of his research said that Cytokines may act on the cells that secrete them and have autocrine action.…”
Section: Discussionmentioning
confidence: 99%
“…12 Al Ozaibi et.al 2020 in one of his research said that corona virus directly infect and damages the spleen leading to splenic abscess and also causes damage to other lymphoid tissues. 13 The cytokines are produced in response to infection by covid 19, there is excessive production of cytokines having antiviral action, the lymphocytes produces lymphokines. Jun-Ming Zhang, et.al 2007 in one of his research said that Cytokines may act on the cells that secrete them and have autocrine action.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal management strategy for splenic abscess remains controversial; to date, the traditional surgical approach involving splenectomy has been the treatment of choice, as reported in the first case of splenic abscess in a patient with SARS-CoV-2 infection. 20 Presently, specific centers consider antibiotics alone as a sufficient treatment option, which is supported by case series with success rates of 75%. 6 Fluid culture and sensitivity analysis of the drained abscess must be performed, being aware that COVID-19 positivity may be associated with unusual causative organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Significant SARS-CoV-2-induced changes were observed when examining spleen samples. A case analysis of a 55-year-old patient with COVID-19 revealed that along with the loss of follicles in the white pulp of the spleen, there was lymphoid hyperplasia and a mosaic structure of the white pulp, i.e., some lymphoid follicles had a normal intact structure, while most of them lacked germinal centers, and in some cases, there was an enlarged mantle zone but no clear marginal zone [ 69 ]. At dissection, postmortem spleens of COVID-19 patients were generally contracted with shrunk capsules and were characterized by blood clots, anemic infarction, and hemorrhages [ 70 ].…”
Section: Structural Impairment Of Lymphoid Tissue In Covid-19mentioning
confidence: 99%